2007
DOI: 10.1177/0044118x06287861
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Effects of Strain on the Delinquency of South Korean Youth

Abstract: General strain theory (GST) was tested as an explanation of violent and status offense delinquency of South Korean girls and boys. One research objective was to determine whether Korean girls and boys differed in their experience of each type of strain and in the levels of conditioning effects that might moderate the connections of strain to delinquency. Another objective was to identify gender differences in the effects of different types of strain, conditioning effects, and interaction terms (Strains × Condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 44 publications
(69 reference statements)
7
75
0
Order By: Relevance
“…Among these, three of the eight were from Western countries: Italy (Froggio and Agnew 2007), Iceland (Sigfusdottir et al 2004), and Greece, Russia, and the Ukraine (Botchkovar et al 2009). The other five studies were all from Asia: the Philippines (Maxwell 2001), China (Bao et al 2007), and South Korea (Moon and Morash 2004;Moon et al 2008;Morash and Moon 2007).…”
Section: Gst and Its Current Empirical Statementioning
confidence: 99%
“…Among these, three of the eight were from Western countries: Italy (Froggio and Agnew 2007), Iceland (Sigfusdottir et al 2004), and Greece, Russia, and the Ukraine (Botchkovar et al 2009). The other five studies were all from Asia: the Philippines (Maxwell 2001), China (Bao et al 2007), and South Korea (Moon and Morash 2004;Moon et al 2008;Morash and Moon 2007).…”
Section: Gst and Its Current Empirical Statementioning
confidence: 99%
“…Exposure to stressful life events has been associated with crime and violence among adults (Broidy 2001;Eitle and Turner 2003;Straus 1980), and delinquency and violence against peers among adolescents (Baker et al 2010;Morash and Moon 2007;Ngo and Le 2007;Youngstrom et al 2003). A number of studies have also found a link between life stressors and the perpetration of intimate partner violence in adulthood (Cano and Vivian 2001;Mason and Smithey 2012;Roberts et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Children's perceptions, as opposed to parental ones, were critical for this study as "the perception of parent style by the child is more important than actual parenting" (Steinberg et al, 1992, p. 32). Primary students in grades four through six were selected to be used for this study because pre-adolescent children are primarily influenced and controlled by family at this age rather than by outside influences such as negative peers (Moon & Morash, 2004;Morash & Moon, 2007;Noyot-Corbitt & Moon, 2010). High academic achievement was verified for each study participant via standardized state English/Language Arts and Mathematics test score reports.…”
Section: Methods and Designmentioning
confidence: 99%